Dialogue with Christians in the views of Sunnah - Gasmelsid, Saadeldin Mansour (s.n, 2012)
The paper touched on the most important basis for dialogue and etiquette that should be upon by the parties, it is that honesty and sincerity and strength of argument and evidence, and with humility and accept the truth from any quarter, and must be in dialogue, frankness and openness and objectivity. And that the dialogue with the other useful and beneficial. The paper is exposed to the first migration of Muslims to Habasha, and what was the discussed between Najjashi and the delegation of (Mushrikeen) infidels the Muslims, led by Lord Ja'far ibn Abi Talib (R.A).